A case study in national library innovation: Newspapers in the British Library. (October 2014) - Stephens, Andy; Brazier, Caroline; Spence, Phil
The British Library's GBP 33m Newspaper Programme, which is now nearing completion, was established to address a range of legacy issues associated with ensuring the long term storage, preservation and access to the UK's national newspaper collection, one of the largest and most comprehensive newspaper collections anywhere in the world with more than 750 million pages of newspapers spanning more than three centuries. The programme has delivered a purpose-built state-of-the-art storage facility, with a fully automated retrieval system and full temperature and humidity control, that will enable the British Library's print newspaper collections to be kept in archival standard conditions for the first time ever. A new service proposition – the Newsroom – has been created at St Pancras which will, through a combination of collecting and connecting and by combining traditional print and microfilm newspaper content with television and radio broadcast news recordings and with web news into an integrated offering, transform the traditional newspaper reading room concept into a hub for news and media. Increased digitization will both enable online access and protect the original newsprint from further wear and tear. The paper reports on a number of innovative solutions which have been adopted in taking the Newspaper Programme forward – in particular in relation to digitization funding models, storage solutions, onsite service provision, and accessibility – and as such it provides a case study in national library innovation.